Gambaran Pengetahuan Self Care Management pada Penderita Hipertensi di Prolanis Puskesmas Grogol - Moch Achnaf Hadyan Al Husain; Siti Fatmawati (PT Pustaka Cendekia Publisher, 2026)
Hypertension remains a major global health challenge, particularly in Indonesia where prevalence reaches 34.1% with high complication risks due to inadequate self-care management knowledge. This study aimed to describe self-care management knowledge among hypertension patients in Prolanis Puskesmas Grogol, Sukoharjo. A quantitative descriptive approach was employed with 74 respondents selected via total sampling from 110 Prolanis participants. Data were collected using the validated Hypertension Self-Management Behavior Questionnaire (HSMBQ) with 20 Guttman scale items and analyzed through univariate frequency distribution via SPSS 25. Results showed majority respondents were middle-aged females (58.1%, 77.0%) with high school education (39.2%) and unemployed (56.8%), possessing good knowledge levels (54.1%), followed by moderate (43.2%) and poor (2.7%). In conclusion, while Prolanis effectively builds foundational knowledge, targeted interventions remain essential for moderate knowledge groups to enhance comprehensive self-care practices and prevent complications.